The Improvement Of English Writing And Students’ Motivation Through Brainstorming - Varia Virdania Virdaus (MOTORIC, 2019)
Brainstorming activity is a main factor that can give effect on students’ writing motivation. Teaching English writing by using brainstorming strategy is really important especially to increase students’ motivation. This research is aimed at investigating the effect of brainstorming and its relation to students’ motivation in English writing for the second semester students of Management Major of STIE Perbanas Surabaya, numbering 25 students in academic year 2018-2019. Classroom Action Research (CAR) method was applied in this research. Researcher could investigate and analyze brainstorming process by using this method. Applying brainstorming strategy, the participants (students) were more motivated in terms of writing, which at this time was English writing with a particular topic. Result of this study revealed that brainstorming strategy could improve students’ English Writing skill and their motivation in writing. They could produce good and effective words, and also interesting answers. Based on the fact, brainstorming strategy is suggested for teaching English Writing. Students’ motivation in writing much higher than without brainstorming strategy. Key Words: Brainstorming, Motivation, English Writing